PENGARUH COOPERATIVE PLAY PUZZLE TERHADAP KEMAMPUAN BERADAPTASI SOSIAL PADA ANAK TUNAGRAHITA - Riskayani Riskayani (LPPMK STIKES Widyagama Husada, 2020)
Background: Retardation was a big world problem, especially for developing countries. The ability to socialize in mental retardation children did not develop optimally which caused the child to be not independent, unable to communicate directly in two directions with friends or other people. Objective: To find out the effect of cooperative play puzzles on the social adaptability of mental retardation children. Method: This study used a quasy experimental design with a pretest posttest one group design approach. The sampling technique used purposive sampling with an instrument in the form of observation of the social adaptation ability checklist sheet. The number of respondents was 10 people. The statistical test used Wilcoxon Sign Rank test to determine the effect of the cooperative play puzzle variable on the social adaptation ability of mental retardation children. Result: Most of the respondents had enough capability of social adaptability before being given play therapy, as many as 6 respondents (60%), and after being given play therapy intervention suggested that almost all respondents were capable to social adaptability, as many as 9 respondents (90%). In the Wilcoxon Sign Rank test, the value of p = 0.004 or H0 was rejected, meaning that there was a significant effect of Cooperative Play Puzzle on the social adaptation ability of mental retardation children.Conclusion: Cooperative play puzzles could improve social adaptability in mental retardation children.